Bipolar disorder and neurophysiologic mechanisms - Simon M McCrea (Dove Medical Press, 2008)
Simon M McCreaDepartments of Neurology and Neuroophthalmology, University of British Columbia, 2550 Willow Street, Vancouver, British Columbia, Canada V5Z 3N9Abstract: Recent studies have suggested that some variants of bipolar disorder (BD) may be due to hyperconnectivity between orbitofrontal (OFC) and temporal pole (TP) structures in the dominant hemisphere. Some initial MRI studies noticed that there were corpus callosum abnormalities within specific regional areas and it was hypothesized that developmentally this could result in functional or effective connectivity changes within the orbitofrontal-basal ganglia-thalamocortical circuits. Recent diffusion tensor imaging (DTI) white matter fiber tractography studies may well be superior to region of interest (ROI) DTI in understanding BD. A “ventral semantic stream” has been discovered connecting the TP and OFC through the uncinate and inferior longitudinal fasciculi and the elusive TP is known to be involved in theory of mind and complex narrative understanding tasks. The OFC is involved in abstract valuation in goal and sub-goal structures and the TP may be critical in binding semantic memory with person–emotion linkages associated with narrative. BD patients have relative attenuation of performance on visuoconstructional praxis consistent with an atypical localization of cognitive functions. Multiple lines of evidence suggest that some BD alleles are being selected for which could explain the enhanced creativity in higher-ability probands. Associations between ROI’s that are not normally connected could explain the higher incidence of artistic aptitude, writing ability, and scientific achievements among some mood disorder subjects.Keywords: bipolar disorder, diffusion tensor imaging, white matter tractography, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, uncinate fasciculus, mood dysphoria, creativity, ventral semantic stream, writing ability, artistic aptitude